Answer:
F.
Step-by-step explanation:
Answer:
-1
Step-by-step explanation:
Tip: Remember to always start from the inside, which would be g(3), in this case.
The first step in solving this problem is to solve for g(3).
To accomplish this, you must substitute 3 for x into the given equation g(x) = x^2 - 10
- g(3) = 3^2 - 10
- g(3) = 9 - 10
- g(3) = -1
The next step is to substitute the answer of g(3), -1, for x in the given equation f(x) = 2x + 1.
Because the equation is asking for f[g(3)], it becomes f(-1) because g(3) = -1.
- f(-1) = 2(-1) + 1
- f(-1) = -2 + 1
- f(-1) = -1
Therefore, f[g(3)], or f(-1), equals -1
121 is the area of the square
1. (2x + 3)(x + 1)
2. Prime
3. (4x - 1)(2x + 3)
4. Prime
5. (2x - 7)(x + 4)